The Impact of Digital Media on Religious Practices and Community Engagement - Elsafir, Rayyanah Putri (Jurnal Ar Ro'is Mandalika (Armada), 2024)
The rapid expansion of digital media has profoundly influenced religious education and identity formation, reshaping how individuals’ access, engage with, and express their religious beliefs. This study examines the transformative role of digital media in these areas, focusing on its impact on the accessibility and interactivity of religious education, as well as its role in the construction and expression of religious identity. Digital platforms, such as online courses, social media, and virtual communities, have democratized religious knowledge, enabling people from diverse backgrounds to engage with religious teachings and practices in flexible and personalized ways. Moreover, digital media has allowed for new forms of self-representation, facilitating the creation of individualized religious identities that blend various traditions and practices. Despite these advancements, the study also highlights the challenges posed by digital media, including the risk of misinformation, commercialization of religious content, and the fragmentation of communal religious practices. This paper concludes by discussing the need for a balanced approach to digital media in religious contexts, ensuring that its benefits are maximized while addressing its potential drawbacks to maintain the authenticity and integrity of religious expression and practice in the digital age.